Piecemeal Journey to ’HALCYON’ World of Computing: From Past Progress to Future Challenges - Seth, R.; Kapoor, R.; Al-Qaheri, H.; Sanyal, S. (Informatica)
Piecemeal Journey to 'HALCYON' World of Computing: From Past Progress to Future Challenges